WEB-BASED LEARNING AND STUDENTS' SCHOLASTIC ACCOMPLISHMENT AT NATIONAL OPEN UNIVERSITY OF NIGERIA - Taofeek Gbolahan Muibi (Інформаційні технології і засоби навчання)
The study examined the impact of Web based learning structures (Moodle, Blackboard, Online Library, Online Course Module/Study Guide, Internet Learning for coach student and Student - Student Connection and Times of Access of Internet Learning Applications) on students' scholarly accomplishment at the National Open University of Nigeria. The descriptive survey research design was used with a population of 100 to 400 students and a sample size of 150 students from the National Open University of Nigeria's schools of law, arts and social science, business and human resources, education, science and technology, and center for continuing education. A questionnaire with 53 questions titled: Experts validated the Online Learning and Learners' Academic Achievement in National Open University of Nigeria Scale (OLLAAS), and Cronbach's alpha yielded a reliability coefficient of 0.76. To test the hypotheses at the 0.05 level of significance, data were analyzed using Multiple Regressions and the Pearson Product Moment Correlation Coefficient. The discoveries of the review uncovered that the Internet learning structures (Moodle, Blackboard, Online Library, Online Course Module/Study Guide, Web based Learning for mentor student and Student - Student Connection and Times of Access of Web based Learning Applications) essentially impacted students' scholarly accomplishment (F (6, 143) = 24.907; R2 = 0.511), and mutually represented 49.1% of its difference. Moodle (r =.206, P0.001), Blackboard (r =.417, P0.001), the Online Library (r =.594, P0.001), the Online Course Module/Study Guide (r =.395, P0.001), online learning for tutor-learner and learner-learner interaction (r =.442, P0.001), and periods of access to online learning applications (r =.625, P0.001) all had positive correlations with students. In light of the discoveries, it was suggested that administration ought to put more in training of this season of computerized age through satisfactory financing to empower schools obtain and introduce ICT foundation. The government and all relevant stakeholders ought to address the problem of incessant power outages. Mechanical gadgets ought to likewise be made accessible to students at sponsored rates to empower everybody partake in remote learning. Web based learning meetings ought to be planned with significant and profoundly captivating and intelligent learning exercises to lessen fatigue among detached students during learning.